2017
DOI: 10.18632/oncotarget.17400
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-like protein 1 promotes inflammatory reactions in nucleus pulposus cells by interacting with the MAPK and NFκB signaling pathways

Abstract: ObjectiveFollistatin-like protein 1 (FSTL1) is a well-known mediator of inflammation. Intervertebral disc disease is an inflammatory disorder. Here, we investigated the role of FSTL1 in the intervertebral discs inflammation.MethodsExpression of FSTL1 in nucleus pulposus tissues from rats and human was determined by immunohistochemistry staining and western blot analysis. The expression levels of tumor necrosis factor-α (TNF-α), interleukin1-β (IL-1β) and matrix metalloproteinase 13 (MMP-13) in human and rat nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…However, this airway inflammation was significantly inhibited by pre-injection of MCC950. [36], [37]. In our study, we demonstrated the pro-inflammatory role of FSTL1 in asthma.…”
Section: Mcc950 Treatment Attenuated Fstl1-induced Activation Of Nlrp3supporting
confidence: 64%
“…However, this airway inflammation was significantly inhibited by pre-injection of MCC950. [36], [37]. In our study, we demonstrated the pro-inflammatory role of FSTL1 in asthma.…”
Section: Mcc950 Treatment Attenuated Fstl1-induced Activation Of Nlrp3supporting
confidence: 64%
“…FSTL1 is known to drive pathology in inflammatory disease settings in mouse models, particularly arthritis (41)(42)(43)(44)(45)(46)(47). Among its various activities, it has been reported to promote inflammatory cytokine production, including IL-1β, from macrophages and fibroblasts (41,47,48). While FSTL1 mRNA was significantly elevated in CLD Linear regression of the top 12 genes that most strongly correlate with ELF score (r 2 value of 0.39 or more), showing gene expression as an independent variable and ELF score as a dependent variable.…”
Section: Resultsmentioning
confidence: 99%
“…This approach revealed 12 such genes ( Figure 6D), 10 of which encoded extracellular proteins (Table 3). Since inflammation, associated cell death, and aberrant wound healing are central to the progression of liver fibrosis in NAFLD (78), we pursued FSTL1 as a steatosis-linked gene, because of its strong links to both inflammation and fibrosis (40,41,(43)(44)(45)79). FSTL1 is a secreted glycopro- Supplemental Table 1 for details of the patient cohort; n = 35; detectable levels in 9 patients; horizontal bars indicate mean ± SEM; circles, early stages; triangles, advanced stages).…”
Section: List Of 11 Degs (With 25-fold Difference In Expression Bementioning
confidence: 99%
“…33 Previous reports showed that FSTL1 stimulate the expression of MMPs in synoviocytes and nucleus pulposus cells. 14,16 Therefore, in this study, we investigated whether FSTL1 affects the expression of MMPs in chondrocytes. Our results showed that FSTL1 significantly increased the expression of MMP-1 and MMP-13 in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%